Association of high TUBB3 with resistance to adjuvant docetaxel-based chemotherapy in gastric cancer: translational study of ITACA-S. Issue 2 (April 2021) - Di Bartolomeo, Maria; Raimondi, Alessandra; Cecchi, Fabiola; Catenacci, Daniel V.T.; Schwartz, Sarit; Sellappan, Shankar; Tian, Yuan; Miceli, Rosalba; Pellegrinelli, Alessandro; Giommoni, Elisa; Aitini, Enrico; Spada, Francesca; et al.
Background: No predictive markers for chemotherapy activity have been validated in gastric cancer (GC). The potential value of class III β-tubulin (TUBB3) as biomarker for prognosis and resistance to taxane-based therapy was reported. Methods: We analyzed GC samples of patients enrolled in the Intergroup Trial of Adjuvant Chemotherapy in Adenocarcinoma of the Stomach (ITACA-S), a randomized adjuvant study comparing 5-fluorouracil/leucovorin (5-FU/LV) and docetaxel-based sequential chemotherapy. TUBB3 was quantitated by selected reaction monitoring mass spectrometry and patients were stratified using a threshold of 750 attomoles per microgram (amol/µg). Cox proportional modeling and Kaplan-Meier survival analysis were used to assess the impact of TUBB3 expression on overall survival (OS) and disease-free survival. Results: Patients with TUBB3 protein levels >750 and <750 amol/µg were 21.9% and 78.1%, respectively, and were well-balanced between treatment arms. TUBB3 protein levels were not prognostic. Whereas no survival differences according to the 2 arms were observed in the subgroup with low TUBB3 expression (5-year OS 47% vs 40%; p = 0.44), patients with high TUBB3 had a clinically meaningful poorer OS when receiving docetaxel-based versus 5-FU/LV chemotherapy (5-year OS 31% vs 54%; p = 0.09), with a statistically significant interaction between TUBB3 and treatment ( p = 0.049). Conclusions: The quantification of TUBB3 might be considered as a negative predictive biomarker of benefit from taxane-based therapy in GC. Studies are needed to evaluate its role in the neoadjuvant setting.